2018
DOI: 10.1039/c7ta09036f
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering of highly stable lanthanide metal–organic frameworks by particle modulation for coating catalysis

Abstract: A powerful strategy to design the structure, control the particle sizes and fabricate catalytic devices is developed for lanthanide MOFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Chen et al developed a size-control strategy to fabricate a novel Ce-MOF (BIT-58) in Figure 8b. [127] After decreasing the particle sizes to nanoscale, the nano-BIT-58 exhibited a more robust catalytic performance compared with BIT-58 toward Knoevenagel condensation reaction.…”
Section: Knoevenagel Condensation Reactionmentioning
confidence: 95%
“…Chen et al developed a size-control strategy to fabricate a novel Ce-MOF (BIT-58) in Figure 8b. [127] After decreasing the particle sizes to nanoscale, the nano-BIT-58 exhibited a more robust catalytic performance compared with BIT-58 toward Knoevenagel condensation reaction.…”
Section: Knoevenagel Condensation Reactionmentioning
confidence: 95%
“…g) Catalytic performances of the film during three catalytic cycles. Reproduced with permission . Copyright 2018, Royal Society of Chemistry.…”
Section: Applications For Mof Nanofibersmentioning
confidence: 99%
“…Chen et al reported the preparation of a lanthanide‐based MOF nanofiber structure in the Knoevenagel condensation, utilizing the MOF BIT‐58 (BIT stands for Beijing Institute of Technology). This MOF has a catalytic active site with a Ce 3+ metal center and 1,3,5‐tris(4‐carboxyphenyl)benzene (BTB) as the organic ligand (Figure d).…”
Section: Applications For Mof Nanofibersmentioning
confidence: 99%
“…Metal‐organic frameworks (MOFs), due to their tunable pore size, high specific surface area, and versatile structures, have received widespread attention and have been applied in many fields, such as catalysts, chemical sensing, gas adsorption, and separation. [ 13–22 ] Integrating MOFs with plasmonic NPs could confine gas directly in the SERS platform, which has preconcentration effect to enhance the SERS signals. [ 23–25 ] More importantly, MOFs coated on the plasmonic NPs could suppress the attenuation of the surrounding electromagnetic field of NPs.…”
Section: Introductionmentioning
confidence: 99%